Glacial isostatic adjustment near the center of the former Patagonian Ice Sheet (48°S) during the last 16.5 kyr. (1st February 2022) - Troch, Matthias; Bertrand, Sebastien; Lange, Carina B.; Cárdenas, Paola; Arz, Helge; Pantoja-Gutiérrez, Silvio; De Pol-Holz, Ricardo; Kilian, Rolf
Abstract: Our understanding of glacial isostatic rebound across Patagonia is highly limited, despite its importance to constrain past ice volume estimates and better comprehend relative sea-level variations. With this in mind, our research objective is to reconstruct the magnitude and rate of Late Glacial and Holocene glacial isostatic adjustment near the center of the former Patagonian Ice Sheet. We focus on Larenas Bay (48°S; 1.26 km 2 ), which is connected to Baker Channel through a shallow (7.4 m) and narrow ( ca. 150 m across) inlet, and hence has the potential to record periods of basin isolation and marine ingression. The paleoenvironmental evolution of the bay was investigated through a sedimentological analysis of a 9.2 m long radiocarbon-dated sediment core covering the last 16.8 kyr. Salinity indicators, including diatom paleoecology, alkenone concentrations and CaCO3 content, were used to reconstruct the bay's connectivity to the fjord. Results indicate that Larenas Bay was a marine environment before 16.5 cal kyr BP and after 9.1 cal kyr BP, but that it was disconnected from Baker Channel in-between. We infer that the postglacial rebound started before 16.5 cal kyr BP and that it outpaced global sea-level rise until slightly before 9.1 cal kyr BP. During the Late Glacial and early Holocene, the center of the former Patagonian Ice Sheet experienced an absolute uplift of ca. 96 m, at an average rate of 1.3 cm/yr. During the remainder of the Holocene, glacial isostatic adjustment continued ( ca. 20 m), but at a slower average pace of 0.2 cm/yr. Comparisons between multi-millennial variations in the salinity indicators and existing records of global sea-level rise suggest that the glacial isostatic adjustment rate also fluctuated within these time intervals, likely in response to glacier dynamics. More specifically, most of the glacial isostatic adjustment registered between 16.5 – 9.1 cal kyr BP seems to have occurred before meltwater pulse 1A (14.5 – 14.0 kyr BP). Likewise, it appears that the highest glacial isostatic rebound rates of the last 9.1 kyr occurred during the late Holocene, most likely in response to glacier recession from their Neoglacial maxima. This implies a relatively rapid response of the local solid earth to ice unloading, which agrees with independent modelling studies investigating contemporary uplift. We conclude that the center of the former Patagonian Ice Sheet experienced a glacial isostatic adjustment of ca. 116 m over the last 16.5 kyr, and that >80% occurred during the Late Glacial and early Holocene. Highlights: 116 m uplift near the center of the former Patagonian Ice Sheet during the last 16.5 kyr. At least 80% of the uplift occurred during the Late Glacial and early Holocene. The average uplift rate was 1.3 cm/yr between 16.5 – 9.1 cal kyr BP. The average uplift rate was 0.2 cm/yr during the last 9.1 kyr.